Transcriptomic Response of Huanglongbing-Infected Citrus sinensis Following Field Application of a Microbial Fermentation Product - Lally, Richard D.; Donaleshen, Kathleen; Chirwa, Ulalo; Eastridge, Katie; Saintilnord, Wesley; Dickinson, Edward; Murphy, Richard; Borst, Steven; Horgan, Karina; Dawson, Karl (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is considered the most destructive disease in Citrus production and threatens the future of the industry. Microbial derived defence elicitors have gained recognition for their role in plant defence priming. This work assessed a 5% (V/V) microbial fermentation application (MFA) and its role in the elicitation of defence responses in HLB infected Citrus sinensis trees following a foliar application with a pump sprayer. Using a PCR detection method, HLB infection levels were monitored in healthy and infected trees for 20 months. Nutrient analysis assessed N, P, K, Ca, Mg, Mn, Zn, Fe, B and Cu concentrations in the trees. MFA significantly increased Cu concentrations in treated trees and resulted in the stabilisation of Disease Index (DI) in infected trees. Initial real time qPCR analysis of defence associated genes showed a significant increase in pathogenesis related protein 2 (PR2) and phenylalanine ammonia lyase (PAL) gene expression in healthy and HLB infected trees in response to MFA. Gene expression of PR2 and PAL peaeked 6 hours post microbial fermentation application during an 8-hour sampling period. A transcriptomic assessment using GeneChip microarray of the hour 6 samples revealed differential expression of 565 genes when MFA was applied to healthy trees and 909 genes when applied infected citrus trees when compared to their respective controls. There were 403 uniquely differentially expressed genes in response to MFA following an intersectional analysis of both healthy and infected citrus trees. The transcriptomic analysis revealed that several genes associated with plant development, growth and defence were upregulated in response to MFA, including, multiple PR genes, lignin formation genes, ROS related genes, hormone synthases and hormone regulators. This study provides further evidence that MFA may play an important role as a plant elicitor in an integrated pest management strategy in citrus and other agronomically important crops.